Pretty boys do not cry: The role of facial expressions on facial attractiveness rating - Barzut, Vesna; Blanuša, Jelena (Psihološka istraživanja, 2023)
Facial attractiveness is the concept that is widely explored in the previous studies. Many research tried to identify key factors that are affecting aesthetic judgment of faces. Some of these factors are symmetry, averageness, and facial expressions. Our study aimed to explore whether the presence of different facial expressions affects aesthetic judgment. A total of 61 students took part in this study. They evaluated female and male faces with expressions of happiness, anger, sadness, or neutral on several scales (Beautiful, Pleasant, Attractive, and Harmonious). Results showed that overall female faces were rated as more attractive, beautiful, and pleasant, but not harmonious. Furthermore, faces with expressions of anger and sadness were rated lower on each scale compared to neutral and happy faces. However, sad male faces were rated lower compared to sad female faces. One of the possible explanations for such a result could be the role of the social context where society discourages the display of certain emotions, particularly for men.